TREN DAN EFEKTIVITAS REALISTIC MATHEMATICS EDUCATION (RME) DALAM MENINGKATKAN LITERASI MATEMATIS: SEBUAH SYSTEMATIC LITERATURE REVIEW - Nurfaidah, Desti; Nandang Mustafa, Ade; Nirmalasari, Dinar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematical literacy is a fundamental challenge in Indonesian education, as reflected in the PISA 2022 achievement, which placed Indonesia in 70th place out of 81 participating countries with an average mathematics score of 366, far below the OECD average of 472. Realistic Mathematics Education (RME), which is based on the view that mathematics is a human activity, is recognized as a contextual approach that has the potential to bridge this gap. However, there has been no systematic synthesis specifically examining the trends and effectiveness of RME on mathematical literacy in the 2020-2026 publication period. This study aims to map research trends and analyze the effectiveness of RME in improving students' mathematical literacy through a Systematic Literature Review (SLR) approach referring to the PRISMA 2020 protocol. Literature searches were conducted in Google Scholar and Scopus databases using the Publish or Perish tool with a combination of structured Boolean keywords. Screening and assessment of the eligibility of articles were managed through Covidence using the PICOS framework, resulting in 46 articles as the final data corpus. The study results show a significant acceleration in publication trends since 2023, with research dominated by junior high school students and quasi-experimental designs. RME has been consistently effective across all levels of education, with N-gain values ​​ranging from 0.29 to 0.80, mostly in the moderate to high category, and large effect sizes in several studies. The integration of RME with digital technology further strengthens this effectiveness. These findings provide a solid empirical foundation for the broader implementation of RME in mathematics education policy and practice, particularly within a competency-based curriculum framework.